“A step towards freedom”? The Spanish anarcho-syndicalism and the first coup d’etat in Argentina - Benclowicz, José Daniel (Hispania Nova, 2020)
This paper examines the representations of Spanish anarcho-syndicalism of a pivotal event in Argentine history: the coup d'etat of 1930, the first since the final political organization of this country. In order to do so, I analyze the reception of the news about the political and social situation in Argentina, charting the evolution of an unexpected and striking sympathy for the military coup, initially presented in the pages of Solidaridad Obrera, the CNT newspaper. A transnational perspective is adopted, which take into account the dialogues and relationships between the different anarchist tendencies on both sides of the Atlantic, as well as the impact of the political context of each country. Thus, in addition to providing an account of the changing positions of the CNT, the article also explores the little known development of Argentine anarchism in this period.
Keywords: Spanish anarcho-syndicalism; Representations of Argentina; First half of the 1930s; Coup d'etat of 1930; Transnational relations